(untitled) (Swiss Medical Weekly, 2012)
Interferons are not only the first line of defence against viral infections such as hepatitis C virus infections, but they also have important roles during the chronic phase of viral infections. For over 20 years now, recombinant interferon alpha has been used for the treatment of chronic hepatitis C. The molecular mechanisms responsible for non-response to interferon are still not completely understood, but systematic analysis of liver biopsies revealed that the spontaneous activation of the endogenous interferon system in the liver of patients with chronic hepatitis C prevented response to interferon-based therapies. Moreover, recent genomewide association studies found a highly significant and strong association between genetic variants near the IFNλ3 gene, designated the IL28B genotype, with spontaneous clearance of hepatitis C virus as well as with response to treatment of chronic hepatitis C with pegylated interferon alpha and ribavirin. The molecular pathways that link the IL28B genotype with antiviral effector systems of the innate and adaptive immune system are not known. However, substantial progress has been made in basic understanding of the induction of interferons through toll-like receptor and RIG-I/MDA5 pathways, and of interferon-induced signalling pathways and antiviral effector systems. Over the last two decades, hepatitis C virus has been an important tool for study of the fundamental aspects of host-virus interactions in a chronic viral infection. Further insights into the viral escape strategies that allow hepatitis C virus to persist for decades despite an ongoing innate and adaptive immune response will eventually allow the rational development of preventive vaccines.